Forensic Medical Examiners’ Role in Resolving Malpractice Claims - Zahraa Khalifa Sobh; Mamdouh Zaki (Arab Journal of Forensic Sciences & Forensic Medicine)
In the last few years, the trends of malpractice claims have escalated worldwide. In many judicial systems, forensic medical examiners manage malpractice lawsuits because of their experience in medical, legal, and ethical aspects of healthcare. They analyze medical records to objectively investigate consent-related issues and verify any neglect or deviations from standard medical care. Then, the extent of harm is evaluated in the surviving cases by determining the degree of resulting infirmity. Judicial penalty and compensation depend on the infirmity’s percentage. In cases involving patient death, comprehensive post-mortem examinations are performed to explore potential medical errors, death causes, and causal relations between error and the occurrence of death. It is essential to consider that evaluating technical errors necessitates the expert opinions of consultants from the same specialties as the accused physicians. The legal obligation for all forensic medicine experts is to provide objective, unbiased, evidence-based medicolegal reports. The ethical commitments include preserving the confidentiality of data of both patients and accused healthcare providers. Also, forensic medical examiners could actively participate in healthcare education to protect medical staff against future malpractice accusations.